Pemanfaatan Lembar Kerja Peserta Didik (LKPD) dalam Pembelajaran Pendidikan Agama Islam di SMP Fatih Bilingual School Banda Aceh - Siregar, Rizky Syahbani; Realita, Realita; Rizal, Zarfi (Jurnal Pendidikan Madrasah, 2025)
This study aims to examine the effectiveness of using Student Worksheets (Lembar Kerja Peserta Didik/LKPD) designed based on the Discovery Learning model in improving students’ learning outcomes across cognitive, affective, and psychomotor domains in Islamic Education (Pendidikan Agama Islam/PAI), particularly on the topic of Rukhsah. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart spiral model, conducted through two action cycles. The research subjects consisted of 14 seventh-grade students at SMP Fatih Bilingual School Banda Aceh. Data was collected through observations of teacher and student activities, as well as learning outcome tests to measure achievement in the three competency domains. The results indicate a significant improvement in students’ learning outcomes in each cycle, encompassing cognitive, affective, and psychomotor aspects. Furthermore, students’ learning engagement and the quality of teacher performance during the instructional process showed consistent improvement. These findings demonstrate that the implementation of LKPD based on the Discovery Learning model contributes positively to enhancing the quality and effectiveness of Islamic Education learning.